Validation of the telephone-administered version of the mediterranean diet adherence screener (Medas) questionnaire - Gregório, Maria João (2020)
Funding: The present project was granted by the Public Health Initiatives Programme (PT06), financed by EEA Grants Financial Mechanism 2009–2014.